Critical measurement issues/challenges in assessing aerobic capacity in youth - Cureton, K. J.; Mahar, M. T. (Research Quarterly for Exercise and Sport, 2014)
We discuss current measurement issues related to tests of aerobic capacity in the FITNESSGRAM®. Interpretation of tests of aerobic capacity is difficult because the criterion measure of aerobic capacity, maximal rate of oxygen uptake (VO2max) expressed relative to body weight, is inversely related to body fatness and body mass index (BMI). This association cannot be easily be eliminated in a way that maintains the units commonly used to express aerobic capacity (i.e., mL/kg·min) and is understandable to typical test users. Requiring the measurement of BMI to predict VO2max creates practical problems for users by: (a) uncoupling the relation of predicted VO2max to physical performance on the 1-mile run/walk (MRW) and the Progressive Aerobic Cardiovascular Endurance Run (PACER) tests, (b) making explicit the influence of body composition on the ability of children to achieve the aerobic capacity healthy fitness zone, and (c) creating a barrier for users who cannot measure height and weight. The use of test equating improved classification agreement between the MRW and PACER tests but required measurement of BMI to estimate aerobic capacity from the PACER. A new equation to predict aerobic capacity that does not require BMI was recently introduced to address user concerns. This change will improve ease of use of the Fitnessgram with little effect on prediction accuracy but will likely result in poorer classification agreement between the MRW and PACER tests. Although considerable progress has been made in addressing issues related to assessment of aerobic capacity in youth, future work is needed to carefully balance the issues of prediction accuracy, test feasibility, and test agreement.